2020
DOI: 10.1016/j.resmic.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Combined antimicrobial use of essential oils and bacteriocin bacLP17 as seafood biopreservative to control Listeria monocytogenes both in planktonic and in sessile forms

Abstract: The antilisterial activity of Thymus vulgaris, Salvia officinalis essential oils (EOs) and bacteriocin bacLP17 (previously isolated from seafood) was determined, using the compounds alone and in combination. The Disk Diffusion, Minimal Inhibitory Concentration (MIC) and Agar Well Diffusion assays were used to evaluate the effectiveness of the compounds against 12 Listeria monocytogenes in planktonic form, whereas the anti-Listeria biofilm activity was determined against the same strains in optical density (O.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…The antibacterial activities of these natural compounds are attributed to the high content of organo-sulfur compounds, including diallyl sulfide (DAS), diallyl disulfide (DADS), diallyl trisulfide (DATS) and their precursors that destroy the structure and the metabolic process of bacterial cells [40][41][42]. Most studies carried out on the antimicrobial activity of natural products against foodborne pathogens have only been performed in cultural substrates, but the structure and composition of foods, as well as conservation conditions, can influence the effectiveness of the antagonistic compounds [15,43,44]. Firouzi et al [45] reported that higher levels of oregano and nutmeg extracts were needed to contain the growth of L. monocytogenes in roast chicken than in culture medium trials, and according to Singh et al [46], the antibacterial activity of both clove and thyme extracts added to a culture broth was significantly lower than that obtained in a food matrix, such as hot dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activities of these natural compounds are attributed to the high content of organo-sulfur compounds, including diallyl sulfide (DAS), diallyl disulfide (DADS), diallyl trisulfide (DATS) and their precursors that destroy the structure and the metabolic process of bacterial cells [40][41][42]. Most studies carried out on the antimicrobial activity of natural products against foodborne pathogens have only been performed in cultural substrates, but the structure and composition of foods, as well as conservation conditions, can influence the effectiveness of the antagonistic compounds [15,43,44]. Firouzi et al [45] reported that higher levels of oregano and nutmeg extracts were needed to contain the growth of L. monocytogenes in roast chicken than in culture medium trials, and according to Singh et al [46], the antibacterial activity of both clove and thyme extracts added to a culture broth was significantly lower than that obtained in a food matrix, such as hot dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them come from spices known for centuries and widely used for seasoning food products. EOs have also been successfully used for reduction of L. monocytogenes not only in vitro, but also in various food model systems (including meat, milk, vegetables and fruits) as published by many authors even in recent years [17,[24][25][26][27][28][29][30][31][32][33][34][35]. Not only EOs are antilisterial, but also various extracts, for example grape extracts (skin, seed, stems, pomace, juice and berries extracts) [36][37][38], blueberries extracts [37], lowbush berries extracts [39], apple skin, olive pomace, olive juice powder extracts [40] and grapefruit seed extract [41], as well as Achillea schurii flowers extracts [42] showed activity against L. monocytogenes.…”
Section: Antilisterial Plant-derived Compoundsmentioning
confidence: 99%
“…Furthermore, numerous studies have reported the synergistic effect of bacteriocins when combined with classic antibiotics [19], polysaccharide nanoparticles [20], phages [21], essential oils [22], organic compounds and preservatives [23]. The association of bacteriocins with such molecules was expected to have beneficial effects in various applications including anticancer [24], antibiofilm [25], antimicrobial [26] and antifungal [22]. Of note, a major advantage of bacteriocins-bioactive substances combinations is the low amount of each molecule requested to obtain the desired effect.…”
Section: Class Imentioning
confidence: 99%
“…In addition, Iseppi et al [25] revealed the effectiveness of thyme (Thymus vulgaris) and sage (Salvia officinalis) EOs, alone or in combination with the bacteriocin bacLP17 against 12 strains of L. monocytogenes. The authors reported that the best antibiofilm effect was observed with the combination of EOs and bacteriocin, compared to both individual treatments and controls [25].…”
Section: Bacteriocins-essential Oils Synergy Are Active Against Pathogenic Bacteriamentioning
confidence: 99%